Systems‐wide analysis of BCR signalosomes and downstream phosphorylation and ubiquitylation - Shankha Satpathy; Sebastian A Wagner; Petra Beli; Rajat Gupta; Trine A Kristiansen; Dessislava Malinova; Chiara Francavilla; Pavel Tolar; Gail A Bishop; Bruce S Hostager; Chunaram Choudhary (Molecular Systems Biology)
Abstract B‐cell receptor (BCR) signaling is essential for the development and function of B cells; however, the spectrum of proteins involved in BCR signaling is not fully known. Here we used quantitative mass spectrometry‐based proteomics to monitor the dynamics of BCR signaling complexes (signalosomes) and to investigate the dynamics of downstream phosphorylation and ubiquitylation signaling. We identify most of the previously known components of BCR signaling, as well as many proteins that have not yet been implicated in this system. BCR activation leads to rapid tyrosine phosphorylation and ubiquitylation of the receptor‐proximal signaling components, many of which are co‐regulated by both the modifications. We illustrate the power of multilayered proteomic analyses for discovering novel BCR signaling components by demonstrating that BCR‐induced phosphorylation of RAB7A at S72 prevents its association with effector proteins and with endo‐lysosomal compartments. In addition, we show that BCL10 is modified by LUBAC‐mediated linear ubiquitylation, and demonstrate an important function of LUBAC in BCR‐induced NF‐κB signaling. Our results offer a global and integrated view of BCR signaling, and the provided datasets can serve as a valuable resource for further understanding BCR signaling networks.